Peningkatan Manajemen Keuangan di UKM: Peran Pelatihan Teknologi Informasi bagi Kelompok Peternak Ayam Berbasis Digital - Ratna Taliupan; Toar Romario Sigar; Prisca Patricia Liem; Silvana Enjelina Bander; Sri Sunarni Sonu; Murni Sulistyaningsih (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study aims to assess the impact of training on the use of information technology, particularly Microsoft Excel, in the preparation of financial statements within small and medium enterprises (SMEs) of the Digital-Based Chicken Farmers Group. Accurate and timely financial management is crucial for business sustainability, yet many SMEs struggle with effectively organizing and compiling their financial reports due to limited technical skills and access to appropriate tools. This research employs a qualitative approach with a descriptive methodology, utilizing interviews, direct observations, and comparative analysis of financial data before and after the training intervention. The training focused on improving participants’ skills in using Microsoft Excel to create income statements, balance sheets, and cash flow reports. The findings indicate a significant enhancement in the ability of SME managers to utilize Excel’s features such as formulas, tables, charts, and data analysis tools. As a result, the financial statements produced became more accurate, timely, and professionally structured. Moreover, the training positively impacted participants' confidence in utilizing digital tools for financial management, enabling better strategic planning and decision-making based on reliable financial data. Despite these improvements, the study also identifies ongoing challenges, such as the need for continuous training and support, particularly in more advanced Excel functions and other relevant software tools. The research concludes that targeted training in digital tools significantly contributes to the enhancement of financial literacy and operational efficiency in SMEs. Furthermore, it underscores the necessity for continuous professional development and the integration of broader digital solutions—including inventory and marketing systems—to support long-term business growth, adaptability, and competitiveness in an increasingly digital economy